1998
DOI: 10.1146/annurev.astro.36.1.435
|View full text |Cite
|
Sign up to set email alerts
|

Dwarf Galaxies of the Local Group

Abstract: ▪ Abstract  The Local Group dwarf galaxies offer a unique window to the detailed properties of the most common type of galaxy in the Universe. In this review, I update the census of Local Group dwarfs based on the most recent distance and radial velocity determinations. I then discuss the detailed properties of this sample, including (a) the integrated photometric parameters and optical structures of these galaxies, (b) the content, nature, and distribution of their interstellar medium (ISM), (c) their heavy-e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

220
3,284
17
13

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 2,200 publications
(3,534 citation statements)
references
References 402 publications
220
3,284
17
13
Order By: Relevance
“…To get the radial velocity map of our observed field, we found the central velocity in the radial velocity profile of each pixel, that has a level above 2 σ the value of the standard background emission, to ensure galaxy membership. (Mateo 1998). The most active region of IC 1613 is located 3 (or 663 pc) North-East from the photometric center.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…To get the radial velocity map of our observed field, we found the central velocity in the radial velocity profile of each pixel, that has a level above 2 σ the value of the standard background emission, to ensure galaxy membership. (Mateo 1998). The most active region of IC 1613 is located 3 (or 663 pc) North-East from the photometric center.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…27) at a distance of ∼1 Mpc from the Milky Way. About thirty luminous satellite galaxies detected within the Milky Way virial radius (∼ 250 kpc) are considered possible cases of cold dark matter substructure, albeit at a much lower abundance than is predicted from simulations 15 .…”
mentioning
confidence: 99%
“…Spirals near the center of the Virgo cluster are deficient in H I gas (Cayette et al 1990(Cayette et al , 1994Chung et al 2009). Also, ; ; Kormendy (1987), van den Bergh (1994b), and Kormendy et al (2009, hereafter KFCB) suggested that Sph galaxies are ram-pressure-stripped dS+Im galaxies, based in part on observations (Einasto et al 1974;van den Bergh 1994avan den Bergh , 1994bMateo 1998) that -with a few (understandable) exceptions -close dwarf companions of Local Group giant galaxies are almost all spheroidals, that distant companions are irregulars, and that galaxies with intermediate (Sph/Im) morphologies live at intermediate distances. Ever since van den Bergh (1976), these ideas provided the interpretation of a parallel sequence classification (Figure 1 here) that was constructed operationally to encode the full range of S0+Sph bulge-to-total luminosity ratios B/T from almost 1 to exactly 0.…”
Section: Environmental Processes Imentioning
confidence: 99%